Linguistic school of Akhmet Baitursynuly: Kasym Tynystanov and the kyrgyz national alphabet of the beginning of the XX century (Eurasian Journal of Philology Science and Education, 2024)
The article compares the linguistic heritage of Akhmet Baitursynuly and the statesman of Kyrgyzstan, the founder of Kyrgyz linguistics Kasym Tynystanov, including their scientific works devoted to the problem of the alphabet and spelling. Considering Tynystanov as a representative of the Baitursynuly linguistic school, the idea and scientific theory of Baitursynuly about the Kyrgyz alphabet and spelling, formed by Tynystanov at the beginning of the twentieth century, is determined. The study took as a source K. Tynystanov's textbook "Book for Reading" (Oku kitabi), published in 1924, and the work "Be Able to read and Write" (Oku-zhazu bil), published in 1927, which analyzes two periods of the Arabic Kyrgyz alphabet of 1912-1924 and 1925-1928 and compares them with the alphabets of Baitursynuly of 1912-1922, 1923-1924, 1925-1929 and his spelling rules. Also presented is K.Tynystanov’s view of the Latin alphabet based on the materials of the First All-Union Turkological Kurultai, held in Baku in 1926. As a result of the research, based on primary sources, the similarity of the alphabet and Kyrgyz spelling of K. Tynystanov with the alphabet and spelling of Akhmet Baitursynuly is proved, as well as the fact that K.Tynystanov is a representative of the linguistic school of A.Baitursynuly.Keywords: A. Baitursynuly, K. Tynystanov, alphabet, spelling, writing.